Solve by Substitution x-2y=-6 , -x+2y=6

Math
,
Add to both sides of the equation.
Replace all occurrences of with in each equation.
Tap for more steps…
Replace all occurrences of in with .
Simplify .
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
Multiply by .
Multiply by .
Combine the opposite terms in .
Tap for more steps…
Add and .
Add and .
Remove any equations from the system that are always true.
Solve by Substitution x-2y=-6 , -x+2y=6
Scroll to top